Electrospinning of agar/PVA aqueous solutions and its relation with rheological properties. (22nd January 2015) - Sousa, Ana M.M.; Souza, Hiléia K.S.; Uknalis, Joseph; Liu, Shih-Chuan; Gonçalves, Maria P.; Liu, LinShu
Graphical abstract: Highlights: Agar/PVA nanofibers were successfully produced by electrospinning. A tubeless spinneret was attached inside the electrospinning chamber, set at 50 °C. PVA was used as co-blending polymer. PVA addition significantly improved the solutions' spinnability. Best nanofibers were obtained with 30/70 and 20/80 agar/PVA blends. Abstract: In this work, we report the successful fabrication of agar-based nanofibers by electrospinning technique, using water as solvent media. A tubeless spinneret was attached inside the electrospinning chamber, operating at 50 °C, to avoid agar gelation. Agar pure solution (1 wt%) showed inadequate spinnability regardless of the used electrospinning conditions. The addition of a co-blending polymer such as PVA (10 wt% starting solution) improved the solutions viscoelasticity and hence, the solutions spinnability. Agar/PVA solutions were prepared with different mass ratios (100/0, 50/50, 40/60, 30/70, 20/80 and 0/100) and electrospun at various sets of electrospinning conditions. Best nanofibers were obtained with 30/70 and 20/80 agar/PVA blends while samples with higher agar contents (50/50 and 40/60 agar/PVA) were harder to process and led to discontinuous fibrous mats. This first set of encouraging results can open a new window of opportunities for agar-based biomaterials in the form of nanofibers.